2021
DOI: 10.3389/fphar.2021.716248
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Photoaging and Anti-Inflammatory Effects of Ginsenoside Rk3 During Exposure to UV Irradiation

Abstract: Ginseng is a widely cultivated perennial plant in China and Korea. Ginsenoside Rk3 is one of the major active components of ginseng and is a promising candidate to regulate skin pigments and exert anti-photoaging effects on skin physiology. Ginsenoside Rk3 was mixed with a cream (G-Rk3 cream) and smeared on the skin of mice. Then, the mice were exposed to ultraviolet (UV) A (340 nm and 40 W) and UVB (313 nm and 40 W) radiation. Special attention was given to the anti-photoaging and anti-inflammatory effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…GS Rk3 may also decrease MDA expression and increase SOD and GSH-Px expression. Taken together, these results suggest that GS may have anti-photoaging properties in the skin ( Nah, 2014 ; Zhang et al, 2014 ; Wan et al, 2021 ). However, the development and utilization of GS is limited by their low bioavailability, poor lipophilicity, and limited transdermal absorption.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…GS Rk3 may also decrease MDA expression and increase SOD and GSH-Px expression. Taken together, these results suggest that GS may have anti-photoaging properties in the skin ( Nah, 2014 ; Zhang et al, 2014 ; Wan et al, 2021 ). However, the development and utilization of GS is limited by their low bioavailability, poor lipophilicity, and limited transdermal absorption.…”
Section: Introductionmentioning
confidence: 63%
“…It has been shown that MMP-1 can degrade collagen Ⅰ and collagen Ⅲ. Moreover, MMP-3 can degrade collagen and elastin in a synergistic way, leading to collagen and elastin rupture ( Lee et al, 2020 ; Wan et al, 2021 ). Therefore, MMP-1 and MMP-3 expression was measured in the rat skin tissue homogenate using ELISA kits ( Figures 5E, F ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortical and subcortical micro-infarcts, scattered white matter disorders have all been connected to these processes. These injuries resulted in demyelination and axonal damage [1][2][3][4]. In addition, the ischemic damaging of the neuronal cells and the development of cerebral micro-hemorrhages of venous origin facilitate neurodegenerative disorders and dementia [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Under a physiological condition, in the cytoplasm, NF‐κB is inactive and binds to the inhibitory protein IκB. Once triggered, IκB kinase phosphorylates and degrades the inhibitory protein IκB, releasing and transferring NF‐κB to the nucleus, where it increases the development of pro‐inflammatory mediators such as TNF‐, IL‐1, and iNOS (Wan et al, 2021; Zhang et al, 2019). Our results proved that γ‐GC decreased the expression of p‐p65, p‐IKK, p‐IκBα, and iNOS both in mice and cells treated with ethanol.…”
Section: Discussionmentioning
confidence: 99%